A ligation and restriction enzyme independent cloning technique: an alternative to conventional methods for cloning hard-to-clone gene segments in the influenza reverse genetics system - Bhat, Sushant (Virol J, 2020)
BACKGROUND: Reverse genetics is used in many laboratories around the world and enables the creation of tailor-made influenza viruses with a desired genotype or phenotype. However, the process is not flawless, and difficulties remain during cloning of influenza gene segments into reverse genetics vectors (pHW2000, pHH21, pCAGGS). Reverse genetics begins with making cDNA copies of influenza gene segments and cloning them into bi-directional (pHW2000) or uni-directional plasmids (pHH21, pCAGGS) followed by transfection of the recombinant plasmid(s) to HEK-293 T or any other suitable cells which are permissive to transfection. However, the presence of internal restriction sites in the gene segments of many field isolates of avian influenza viruses makes the cloning process difficult, if employing conventional methods. Further, the genetic instability of influenza gene-containing plasmids in bacteria (especially Polymerase Basic 2 and Polymerase Basic 1 genes; PB2 and PB1) also leads to erroneous incorporation of bacterial genomic sequences into the influenza gene of interest. METHODS: Herein, we report an easy and efficient ligation and restriction enzyme independent (LREI) cloning method for cloning influenza gene segments into pHW2000 vector. The method involves amplification of megaprimers followed by PCR amplification of megaprimers using a bait plasmid, DpnI digestion and transformation. RESULTS: Hard-to-clone genes: PB2 of A/chicken/Bangladesh/23527/2014 (H9N2) and PB1 of A/chicken/Bangladesh/23527/2014 (H9N2), A/chicken/Jiangxi/02.05YGYXG023-P/2015 (H5N6) and A/Chicken/Vietnam/H7F-14-BN4–315/2014 (H9N2) were cloned into pHW2000 using our LREI method and recombinant viruses were subsequently rescued. CONCLUSION: The LREI cloning procedure represents an alternative strategy for cloning influenza gene segments which have internal restriction sites for the enzymes used in reverse genetics. Further, the problem of genetic instability in bacteria can be alleviated by growing recombinant bacterial cultures at a lower temperature. This technique can be applied to clone any influenza gene segment using universal primers, which would help in rapid generation of influenza viruses and facilitate influenza research and vaccine development.